Tumor immune microenvironment and apoptotic markers in breast cancer patients carrying BRCA1 gene mutations - A. I. Stukan; A. Yu. Goryainova; O. Yu. Chukhray; S. D. Maksimenko; E. N. Imyanitov; S. V. Sharov; Z. K. Khachmamuk (ABV-press, 2022)
Background. It is suggested that defects in BRCA1 / 2 genes contribute to a high mutational load and high immunogenicity, which modulates immune microenvironment. At the same time, it was shown that BRCA1 / 2-associated breast cancer tumors do not belong to the category of immunoactive ones. These tumors have low expression of immune response genes and exhibit an immunosuppressive type of microenvironment. This indicates the need of antitumor immune response modulation and maintaining of the optimal balance of tumor CD4/CD8 T-lymphocytes ratio. In addition, there is evidence of the additional evaluation of TP53 mutation in these tumors and disruption of the cell death process, which can also be a factor of resistance to therapy, including PARP inhibitors, and serve as a therapeutic target.Materials and methods. The prospective study included 20 patients with BRCA1-associated breast cancer. BRCA1 / 2 mutations (BRCA1 185delAG, 4153delA, 5382insC, 3819delGTAAA, 3875delGTCT, 300T>G, 2080delA, BRCA2 6174delT) were detected in by real-time polymerase chain reaction. Immunohistochemical study was performed on paraffin embedded tissue blocks by an automated method on a ThermoScentific immunohistotainer using monoclonal antibodies. The expression of markers of tumor-infiltrating CD4+ and CD8+ T-lymphocytes, markers of macrophages (CD68, CD163), apoptosis (Bcl-2, p53), cell adhesion markers (E-cadherin, β-catenin) in breast cancer in carriers of BRCA1 mutations was assessed.Results. High CD4/CD8 ratio, which characterizes immunosuppressive microenvironment, occurred in 75 % of cases. BRCA1 5382insC mutation is associated with high level of CD4+ TILs (p˂0.05), G2 is associated with a low CD4/CD8 ratio (p = 0.039) and a high level of CD163 (p = 0.02, AUC = 0.739); T1 correlates with high levels of CD8+ TILs (p = 0.038) and high levels of CD163 (p = 0.033). High Ki-67 is associated with a lack of Bcl-2 expression (p = 0.04) and a low level of E-cadherin (p = 0.02). Negative expression of Bcl-2 occurred in 75 % of cases. High level of p53 expression has been described as the main type of expression in these tumors, suggesting a combination of TB53 and BRCA1 mutations and a violation of cell death mechanism of in these tumors.Conclusion. Breast cancer tumors of patients with hereditary mutations in BRCA1 gene demonstrate immunosuppressive type of microenvironment and a violation of the cell death mechanism. The main directions of future therapy of these tumors may include tumor immune microenvironment modification and activation of cell death mechanisms.